2023
DOI: 10.21037/tlcr-22-515
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of different therapies for brain metastases of non-small cell lung cancer: a systematic review and meta-analysis

Abstract: Background: As one of the most common causes of death in advanced non-small cell lung cancer (NSCLC), brain metastases (BM) have attracted attention and debate about treatment options, especially for patients with negative driver genes or resistance to targeted agents. Therefore, we conducted a meta-analysis to investigate the potential benefit of different therapeutic regimens for intracranial lesions in non-targeted therapy NSCLC patients.Methods: A comprehensive search was conducted in databases including P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 61 publications
(68 reference statements)
1
7
0
Order By: Relevance
“…Of course, such an aggressive strategy may also be associated with more side-effects, therefore prospective validation will be necessary before it can be widely recommended. Nonetheless, this concept is certainly plausible and, besides the current meta-analysis by Chen et al ( 6 ), additionally supported by at least two further important arguments: first, a similar strategy combining ipilimumab/nivolumab with upfront brain RT is the treatment of choice for patients with BM from melanoma, another tumor characterized by high tumor mutational burden (TMB) and particular sensitivity to immunotherapy, like NSCLC ( 7 ); second, the Checkmate-9LA trial has shown better efficacy for the combined nivolumab/ipilimumab-based chemoimmunotherapy compared to standard triplet chemoimmunotherapies for NSCLC in the cross-trial comparison with other phase 2 and 3 studies ( Table 1 ) ( 8 - 11 ). Whether the alternative anti-PD-L1/CTLA-4-based chemoimmunotherapy of the POSEIDON study may be equally able to prolong the duration of intracranial responses as the Checkmate 9LA regime, remains unclear at present.…”
mentioning
confidence: 76%
See 4 more Smart Citations
“…Of course, such an aggressive strategy may also be associated with more side-effects, therefore prospective validation will be necessary before it can be widely recommended. Nonetheless, this concept is certainly plausible and, besides the current meta-analysis by Chen et al ( 6 ), additionally supported by at least two further important arguments: first, a similar strategy combining ipilimumab/nivolumab with upfront brain RT is the treatment of choice for patients with BM from melanoma, another tumor characterized by high tumor mutational burden (TMB) and particular sensitivity to immunotherapy, like NSCLC ( 7 ); second, the Checkmate-9LA trial has shown better efficacy for the combined nivolumab/ipilimumab-based chemoimmunotherapy compared to standard triplet chemoimmunotherapies for NSCLC in the cross-trial comparison with other phase 2 and 3 studies ( Table 1 ) ( 8 - 11 ). Whether the alternative anti-PD-L1/CTLA-4-based chemoimmunotherapy of the POSEIDON study may be equally able to prolong the duration of intracranial responses as the Checkmate 9LA regime, remains unclear at present.…”
mentioning
confidence: 76%
“…Thus, continued CTLA-4 blockade appears to be important for the durability of intracranial responses in NSCLC, whereas RT improves their depth, as suggested by the findings of Chen et al ( 6 ). The use of RT to augment ICI efficacy is an area of intense investigation currently: goal is to heat-up the tumor microenvironment (TME) by inducing local inflammation, which may improve priming, trafficking and the effector function of tumor-reactive T cells ( 13 , 14 ).…”
mentioning
confidence: 82%
See 3 more Smart Citations